Effects of Taiji Stick exercise on strength, balance, and activities of daily living in older adults: a randomized controlled trial - Cao, Longfei; Dong, Xiaoxiao; Qi, Kai; Zhou, Chunhui; Chen, Aiguo (Frontiers in Public Health, 2025)
BackgroundWith advancing age, older adults experience an accelerated decline in physical function. The progressive decline not only compromises overall well-being but also precipitates numerous serious complications, including an increased likelihood of falls and bone injuries, and in more advanced stages, a diminished ability to carry out daily tasks independently. Numerous studies have shown that engagement in Health Qigong and Taijiquan exercises contributes to better physical functioning and facilitates the completion of everyday activities in senior populations. The positive outcomes observed in previous studies provide the theoretical foundation and practical basis for the current investigation. An 11-week Taiji Stick exercise regimen was implemented to explore its impact on grip and lower limb strength, dynamic balance, and daily functional activities in older individuals.MethodsA randomized controlled design was employed. Thirty-five older adults were randomly assigned to either an intervention group or a control group. The intervention group engaged in an 11-week Taiji Stick exercise program, held three times weekly for 45 min per session. Participants in the control group continued with their routine daily activities without receiving any form of intervention. Grip strength was assessed using a portable digital dynamometer. Lower limb muscular strength was evaluated through the Five Times Sit-to-Stand test (5STS), while dynamic balance was measured via the Timed Up and Go test (TUG). The Barthel Index served to examine participant’s activities of daily living (ADL).Results(1) After the intervention, the experimental group showed no significant change in right-hand grip strength [pre-test: 19.00 (15.65, 24.45), post-test: 19.40 (16.15, 25.20); p = 0.185, |r| ≈ 0.32], whereas the control group exhibited a significant decrease in right-hand grip strength [pre-test: 17.15 (14.18, 23.68), post-test: 16.75 (13.03, 23.48); p = 0.001, |r| ≈ 0.79]. (2) Following the intervention, the experimental group demonstrated significant improvements in lower limb strength [pre-test: 15.00 (13.40, 20.00), post-test:12.30 (9.55, 15.20); p < 0.001, |r| ≈ 0.86], dynamic balance (pre-test: 15.13 ± 4.04, post-test: 11.77 ± 3.42; p < 0.001, ηp2 = 0.618), as well as in daily living capacity [pre-test: 95.00 (90.00, 100.00), post-test: 95.00 (92.50, 100.00); p < 0.05, |r| ≈ 1.00]. In comparison, the control group experienced a marked decline in lower limb strength [pre-test:16.40 (14.75, 20.85), post-test:17.50 (15.50, 23.25); p < 0.001, |r| ≈ 0.88], as well as a notable deterioration in activities of daily living [pre-test: 95.00 (88.75, 100.00), post-test: 90.00 (80.00, 95.00); p < 0.01, |r| ≈ 0.89], along with a non-significant reduction in dynamic balance was noted (pre-test:17.16 ± 3.92, post-test:17.92 ± 4.70; p > 0.05, ηp2 = 0.081).ConclusionAn 11-week Taiji Stick exercise program can effectively enhance lower limb strength and dynamic balance, maintain upper limb strength, show potential to reduce fall-related risks, and improve daily living ability in older adults.Clinical trial registrationThis study was approved for registration by the Chinese Clinical Trial Registry on April 24, 2024 (ChiCTR2400083424).